Evaluation of the management function and its projection in the evaluation of the center. Model of the Community of Madrid - Barbero Alcalde, Ana María; Secadura Navarro, Tomás (Avances en Supervisión Educativa, 2023)
The article presents the evaluation model for the management function in non-university public educational centers that is currently being carried out in the Community of Madrid. The main characteristic of this evaluation procedure is to be a matrix reference of the current General Multiannual Action Plan (2021-2025) for the Educational Inspection. Furthermore, it is a model proposed to contribute both to the assessment of the professional practice and the mandate of directors, as well as to the global and comprehensive evaluation of the educational center, and to the improvement of the Community of Madrid educational system as a whole. As a working method, the structure of the type of evaluation and the technical protocol applied (principles, purpose, tools, phases, agents and evaluation criteria) have been studied, together with the analysis of the results obtained. Finally, the robustness of this evaluation model for the management function is acknowledged, but nuances and proposals for improvement are also provided in view of the difficulties and weaknesses found.